Seafloor spreading and tectonics at the Charlie Gibbs transform system (52-53ºN, mid atlantic ridge): Preliminary results from R/V A. N. Strakhov expedition S50 - Skolotnev S. G.; Sanfilippo A.; Peyve A. A.; Nestola Y.; Sokolov S. Yu.; Petracchini L.; Dobrolyubova K. O.; Basch V.; Pertsev A. N.; Ferrando C.; Ivanenko A. N.; Sani C.; et al. (Edizioni ETS, 2021)
The Charlie Gibbs offsetting by ~ 340 km the Mid Atlantic Ridge (MAR) axis at 52°-53° N is one of the main transform systems of the North Atlantic. Located between long mid-ocean ridge segments influenced from the south by the Azores and from the north by the Iceland mantle plumes, this transform system has been active since the early phases of North Atlantic rifting. Object of several surveys in the ’70 and ’80, Charlie Gibbs received great attention for its unique structure characterized by two long-lived right-lateral transform faults linked by a short ~ 40 km-long intra-transform spreading centre (ITR) with parallel fracture zone valleys extending continuously towards the continental margins. In October 2020 expedition S50 of the R/V A.N. Strakhov surveyed an area of 54,552 km2 covering the entire Charlie Gibbs transform system and the adjacent MAR spreading segments. We collected new bathymetric, magnetic and high-resolution single channel seismic data, along with basaltic, gabbroic and mantle rocks from 21 dredges. This work contains preliminary data from cruise S50 and discusses the large-scale architecture of this unique, long-lived transform system.